Cost-effectiveness of olaparib versus routine surveillance in the maintenance setting for patients with BRCA-mutated advanced ovarian cancer after response to first-line platinum-based chemotherapy in Singapore - Tan, David SP (Asian Society of Gynecologic Oncology; Korean Society of Gynecologic Oncology and Colposcopy, 2021)
10.3802/jgo.2021.32.e27